2015
DOI: 10.1002/cvde.201507171
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Flexible SiC Nanowires by Fluidized Bed Chemical Vapor Deposition

Abstract: High flexible SiC nanowires with diameters in the range of 10 to 50 nm and lengths of several hundred micrometers to several millimeters are synthesized using a novel catalyst-assisted fluidized bed chemical vapor deposition method. Methyltrichlorosilane (MTS) is used as source material and particles containing cobalt were used as catalyst. The fluidized bed is specially designed to form a perpendicular uneven temperature distribution. Suspended nanosized liquid catalyst droplets are produced at middle high te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…These properties make SiC NWs a promising candidate material for many applications, such as reinforcement material for ceramics/metals, field‐emission devices, hydrogen sensor, and photoelectrocatalysts etc. Until now, SiC NWs have been synthesized in the high vacuum closed system by various techniques, for instance, carbon nanotube template, chemical vapor deposition, sol‐gel process, thermal evaporation, carbothermal reduction and molten salt method etc. Liu et al reported the high flexible SiC NWs synthesized by a catalyst‐assisted fluidized bed chemical vapor deposition method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties make SiC NWs a promising candidate material for many applications, such as reinforcement material for ceramics/metals, field‐emission devices, hydrogen sensor, and photoelectrocatalysts etc. Until now, SiC NWs have been synthesized in the high vacuum closed system by various techniques, for instance, carbon nanotube template, chemical vapor deposition, sol‐gel process, thermal evaporation, carbothermal reduction and molten salt method etc. Liu et al reported the high flexible SiC NWs synthesized by a catalyst‐assisted fluidized bed chemical vapor deposition method.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, SiC NWs have been synthesized in the high vacuum closed system by various techniques, for instance, carbon nanotube template, chemical vapor deposition, sol‐gel process, thermal evaporation, carbothermal reduction and molten salt method etc. Liu et al reported the high flexible SiC NWs synthesized by a catalyst‐assisted fluidized bed chemical vapor deposition method. Tony et al reported a novel synthesis of SiC nanotubes by microwave heating of blended silicon dioxide and multi‐walled carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…SiC nanowires show high growth orientation, high melting point, good mechanical property, high elastic modulus, small thermal expansion coefficient, good chemical stability. It can be used in high temperature, high frequency, high power, and corrosive environments [1,2].…”
Section: Introductionmentioning
confidence: 99%